2020
DOI: 10.1101/2020.06.28.175810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human vault RNA enhances tumorigenesis and chemoresistance through the lysosome

Abstract: The small non-coding vault RNA (vtRNA) 1-1 has been shown to confer apoptosis resistance in several malignant cell lines and also to modulate the autophagic flux in hepatocytes, thus highlighting its pro-survival role. Here we describe a new function of vtRNA1-1 in regulating in vitro and in vivo tumor cell proliferation, tumorigenesis and chemoresistance. By activating extracellular signal-regulated kinases (ERK 1/2), vtRNA1-1 knock-out (KO) inhibits transcription factor EB (TFEB), leading to a downregulation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“… Vault RNAs are abundantly expressed in liver samples. Northern blot analysis in paired patient-derived tissues was performed as described in [ 53 ] and revealed that vtRNA1-1 and vtRNA1-2 are expressed in metastatic but not in non-pathological adjacent liver tissues; healthy (H), tumor (T) and metastasis (M). 5.8S rRNA serves as internal loading control.…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“… Vault RNAs are abundantly expressed in liver samples. Northern blot analysis in paired patient-derived tissues was performed as described in [ 53 ] and revealed that vtRNA1-1 and vtRNA1-2 are expressed in metastatic but not in non-pathological adjacent liver tissues; healthy (H), tumor (T) and metastasis (M). 5.8S rRNA serves as internal loading control.…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
“…This regulation of exosomes carried out by MVP indirectly affects the efficacy of chemotherapy treatment and the tumor progression of colon cancer. MVP has also been reported to contribute to temozolomide (TMZ)-resistance in glioblastoma [ 53 ]. The expression of MVP increased in glioblastoma with TMZ resistance, and its sensitivity to the drug was inhibited by increased MVP.…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%